Minimnya Pemeberian Ruang Partisipan serta Transparansi oleh DPR Kepada Rakyat dalam Pembuatan Undang-Undang - Dania Maulinda; Tarisa Dinar Alifia; Syahrul Rizqi Ramadhan; Ulfa Kurnia Sari; Monica Maharani Dewi; Alfian Respamuji (International Forum of Researchers and Lecturers, 2024)
The principle of transparency is one of the important elements that must be present in the formation of laws. With this open principle, the public will know how the law works from planning to the stipulation stage to ratification. As the purpose of the formation of the law itself is to improve the welfare of society, community participation is very necessary so that the laws enacted provide benefits and justice for them. The legislative institution, like the DPR, must be the people's representative in obtaining justice. However, the reality so far is that the community feels that the making of this law is far from the aspirations of the people, the community feels that the government authorities, in this case the DPR, DPRD and the government as the law-forming authorities, are considered to be lacking in implementing the principle of transparency and tend to take advantage of the government. Alone. This research is normative legal research. The main focus of this research is on applicable legal norms, such as the constitution, codification, government regulations, presidential regulations, and others.